MENINGKATKAN KETERAMPILAN BERBICARA MENGGUNAKAN SISTEM THERAPY DOLL (SPIDOL) PADA PESERTA DIDIK SEKOLAH DASAR - Nofrianni, Elvima; Prahagia, Yelvia; Zunarti, Rita (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
Speaking skills are very controversial in the world of education. The technique for carrying out the speaking process at the elementary school level is still not in accordance with the rules, there are still many students in the speaking process who convey ideas that are not fluent and clear, and attitudes and focus on the conversation are not visible in the speaking process. This has an impact on students' speaking techniques towards speaking skills. This study concentrates on developing speaking skills through the correct technique through the therapy doll (marker) system in grade V students. The study was conducted at SDN 81/II Cadika Kec.Bungo, involving 18 students consisting of 12 males and 8 females who were registered in the 2024/2025 academic year. This study applies the type of classroom action research following the Arikunto model which consists of two cycles. Each cycle is carried out in two sessions in class and consists of four steps, namely planning, implementation, observation, and reflection. The research findings show that in cycle I, individual absorption reached 40.80%, while classical learning completion reached 24.01%. There was a significant increase in cycle II, individual abilities increased by 70.40% and classical learning completion reached 70.27%. Based on the results obtained, it was concluded that learning with the application of the Therapy Doll System (SPIDOL) method can improve the speaking ability of fifth grade elementary school students.